Hypercalcaemia, renal failure, anaemia and osteolytic lesions (CRAB) in chronic lymphocytic leukaemia mimicking multiple myeloma. Issue 3 (2nd March 2021) - Panda, Tribikram; Aggarwal, Mukul; Mallick, Saumyaranjan; Dass, Jasmita
Abstract : Classical CRAB features (hypercalcaemia, renal failure, anaemia, osteolytic lesions) have been traditionally defined in patients with plasma cell dyscrasia. But these can be rare and uncommon presentations of other chronic lymphoproliferative disorders (CLPD). The pathophysiological basis of CRAB features in other CLPD need to be explored further for better outcomes and therapeutic interventions. These can present a diagnostic dilemma and requires extensive workup to rule out coexisting malignancy and myeloma. Here, we report an unusual case of B CLPD in a middle-aged male who presented with classical CRAB features along with a brief literature review. After detailed investigations, he was diagnosed as chronic lymphocytic leukaemia, without any second malignancy and responded well to ibrutinib-based therapy.